MiR-338-5p Inhibits EGF-Induced EMT in Pancreatic Cancer Cells by Targeting EGFR/ERK Signaling - Sun, Jian; Chen, Lin; Dong, Ming (Frontiers in Oncology, 2021)
The epidermal growth factor (EGF) pathway plays critical roles during cancer cell epithelial-mesenchymal transition (EMT) process and metastasis. EGFR, as one of the important receptors of EGF, undergoes autophosphorylation with the stimulation of EGF and activates MAPK/ERK, PI3K/Akt/mTOR and other pathways. Here, we identified EGFR was a target of miR-338-5p. Upon EGF treatment, overexpression of miR-338-5p not only downregulated EGFR expression and inhibited MAPK/ERK signaling, but also inhibited EMT and metastasis process of pancreatic cancer (PC) cells. In the clinical pathological analysis, miR-338-5p was significantly down-regulated in 44 pairs PC tissues and its expression was negatively associated with lymph node metastasis and AJCC stage. Furthermore, Overexpression of EGFR partially reversed the protective effect of miR-338-5p overexpression on EGF-mediated migration and invasion in PC cells. Taken together, miR-338-5p controls EGF-mediated EMT and metastasis in PC cells by targeting EGFR/ERK pathways. Here, we hope to provide new insights into the molecular mechanisms of pancreatic cancer, and may help facilitating development of EGFR-based therapies for human cancer.